The Development Strategies for the Culinary Industry Typical of the City of Cirebon in the Era of Disruption - Malau, Alfito Martogi; Yana, Enceng; Rusdiyana, Rusdiyana (Postgraduate, University of Mataram, 2024)
Cirebon has various types of culinary specialties that are spread in various regions, especially in the city of Cirebon. Cirebon culinary specialties certainly have a strategic contribution to Cirebon itself. The emergence of various culinary industries, both traditional and modern, which are developing at this time, will certainly have an impact on the existence of Cirebon culinary specialties. Various efforts have been made by Cirebon MSME players so that Cirebon culinary specialties can continue to compete. The purpose of this study was to determine the creative industry business development strategy in the disruption era carried out by business actors in Cirebon. This research is a literature study research by reviewing the results of previous research on culinary industry business development strategies in Cirebon City. The results of this literature review are that in developing certain products, attractive labeling and packaging are carried out, marketing online through social networks, making testimonials in the form of videos uploaded on YouTube and marketplaces or online stores. Based on the findings of the literature review that several culinary business development strategies typical of Cirebon, namely (1) Application of the Pentahelix model, (2) Promotion and Marketing through print media, (3) Promotion and Marketing television, (4) Increasing the Competence of Business Actors, (5) Promotion and marketing conventionally, (6) Creation of Culinary Atmosphere, (7) Culinary Artibut, and (8) Serving techniques.